One small town, one crazy coach : the Ireland Spuds and the 1963 Indiana high school basketball season - Roos, Mike, 1952- (Bloomington : Quarry Books. an imprint of Indiana University Press, 2013)
In the summer of 1962, the peripatetic and irrepressible Pete Gill was hired on a whim to coach basketball at tiny Ireland High School. There he would accomplish, against enormous odds, one of the great small-town feats in Indiana basketball history. With no starters taller than 5'10", few wins were predicted for the Spuds. Yet, after inflicting brutal preseason conditioning, employing a variety of unconventional motivational tactics, and overcoming fierce opposition, Gill molded the Spuds into a winning team that brought home the town's first and only sectional and regional titles.
Gloomsday -- No Irish in Ireland -- Neither a Drunkard Nor a Bank Robber -- Baptisms -- Turkey Run and the White Horse Tavern -- A Wop and a Wimp and a Moon -- Too Much Is Not Enough -- Life under the Knife -- Ice Man -- Your Blood, Your Sweat, Your Tears -- Drill, Baby, Drill! -- Soap and Towel and Wings of Fire -- Highway 61 Revisited -- The Buy In -- Devil in Blue Jeans -- Coal for Christmas -- I'd Like to Teach the World to Sing -- Of Jeeps and Giants -- The Dude -- Preliminaries -- Walk Like a Man -- The Prophet's Vision -- Divine Insanity -- Keep Your Pants On -- The Axe Just Fell -- Fame -- Small Potatoes -- Invasion of the Little Green Men -- Epilogue.
Print version record.
English.
JSTOR
Keywords: School sports -- Indiana -- History; Basketball -- Indiana -- History; Sports scolaires -- Indiana -- Histoire; GAMES -- Gambling -- Sports; SPORTS & RECREATION -- Business Aspects; SPORTS & RECREATION -- Essays; SPORTS & RECREATION -- History; SPORTS & RECREATION -- Reference; TRAVEL -- Special Interest -- Sports; SPORTS & RECREATION -- Basketball; Basketball; School sports; Indiana; History